The world upside-down in 16th century French literature and visual culture - Robert-Nicoud, Vincent Corentin, 1987- (Faux titre, 2018)
"In The World Upside-Down in 16th Century French Literature and Visual Culture Vincent Robert-Nicoud offers an interdisciplinary account of the topos of the world upside-down in early modern France. To call something 'topsy-turvy' in the sixteenth century is to label it as abnormal. The topos of the world upside-down evokes a world in which everything is inside-out and out of bounds: fish live in trees, children rule over their parents, and rivers flow back to their source. The world upside-down proves to be key in understanding how the social, political, and religious turmoil of sixteenth-century France was represented and conceptualised, and allows us to explore the dark side of the Renaissance by unpacking one of its most prevalent metaphors"--